PENGARUH PENGAMBILAN KREDIT TERHADAP PENDAPATAN USAHATANI TEBU DI KOPERASI SIDO MAKMUR KECAMATAN PAKEM KABUPATEN SLEMAN - , NANI WIJAYANTI; , Dr. Ir. Lestari Rahayu Waluyati, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aims of this research are (1) to find out sugarcane farmers reason of taking credit in cooperation and credit allocation taken by the farmers (2) to find out the factors that influence the number of credit taken by the farmers (3) to find out the impact of taking credits towards sugarcane farmers income. The basic method of this research is descriptive analysis. The respondents are determined purposively, 30 respondents which are the member of Sido Makmur cooperation. The data analysis has been done by ranking scale method to find out the farmers reason in taking credits in cooperation, the Ordinal Least Square regression method is used to find out the factors which determine credit amount taken by the farmers. Cross tab is used to find out the credits determination towards farmers income. The result of this research show that (1) the most reasons chosen by the farmers in taking credits in Sido Makmur cooperation was because the procedure is uncomplicated (2) the land area and the number of labor factors significantly determine in positive degree, meanwhile the own capital factor, farm income, off-farm income determine significantly in negative degree towards the amount of credit taken (3) sugarcane farmers who took the accelerated credits and KKPE have income bigger than the farmers who took only the accelerated credits or only the KKPE.